The owl who became the moon - London, Jonathan, 1947-; Rand, Ted (New York : Dutton Children's Books, 1993)
While riding on a train at night, a young boy listens and watches as he passes by many creatures in their wilderness homes.
Elem. School Library Collection
School Library Journal
Book Links (A.L.A.)
2.5
K-3
Keywords: Night -- Fiction; Railroads -- Trains -- Fiction; Animals -- Fiction; Night -- Fiction; Railroads -- Fiction; Animals -- Fiction; Owls -- Fiction